2015
DOI: 10.1021/acs.chemmater.5b01234
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Defects in Crystalline Lithium-Ion Battery Electrodes by Solid-State NMR: Applications to LiVPO4F

Abstract: Identifying and characterizing defects in crystalline solids is a challenging problem, particularly for lithium-ion intercalation materials, which often exhibit multiple stable oxidation and spin states as well as local ordering of lithium and charges. Here, we reveal the existence of characteristic lithium defect environments in the crystalline lithium-ion battery electrode LiVPO 4 F and establish the relative sub-nanometer-scale proximities between them. Well-crystallized LiVPO 4 F samples were synthesized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 41 publications
9
84
0
1
Order By: Relevance
“…Kosova et al 11 suggested more recently that these extra signals would correspond to the three Li sites of the anti-Nasicon Li3V2(PO4)3, which could be present as impurity, even though their positions do not match exactly those reported in other studies 3,12 . In fact, recently 13 , using 2D 7 Li NMR experiments, we could show that the additional signals correspond to Li sites close to structural and/or chemical defects in LiVPO4F, and not to Li in impurity phases as suggested previously 11 . We thus considered several structural and chemical hypotheses for modeling the defects in LiVPO4F and compared the resulting calculated Fermi contact shifts with the experimental ones.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Kosova et al 11 suggested more recently that these extra signals would correspond to the three Li sites of the anti-Nasicon Li3V2(PO4)3, which could be present as impurity, even though their positions do not match exactly those reported in other studies 3,12 . In fact, recently 13 , using 2D 7 Li NMR experiments, we could show that the additional signals correspond to Li sites close to structural and/or chemical defects in LiVPO4F, and not to Li in impurity phases as suggested previously 11 . We thus considered several structural and chemical hypotheses for modeling the defects in LiVPO4F and compared the resulting calculated Fermi contact shifts with the experimental ones.…”
Section: Introductionsupporting
confidence: 67%
“…LiVPO4F exhibits a Tavorite-type structure described in (Figure 2c) 10,13 . In the following, we will first interpret the main signal located at 116 ppm for the Li site in LiVPO4F based on calculated 3D spin density maps.…”
Section: Resultsmentioning
confidence: 99%
“…[47] As in olivine-type materials,the presence of defects blocks the 1D channels and the rate is determined by the diffusion of the Li + around the defects. [102] It was shown that the elimination of anti-site defects leads to as ignificant improvement of electrochemical performance of LiVPO 4 F. [103] Tw oL i + sites exist in the LiFeSO 4 Fu nit cell occupying positions in the tunnels that run along the [100] and [010] directions.Itwas found that the lowest activation energy for Li + diffusion is 0.36-0.46 eV,s uggesting ah igh Li + mobility. [104] Them ost favorable migration paths are formed from zigzag jumps of Li + allowing the long-range diffusion along the [100],[ 010],a nd [111] directions.T hese interconnected paths create a3 Dd iffusion network leading to the good electrochemical performance of the LiFeSO 4 Fmaterial.…”
Section: Tavorite-typementioning
confidence: 99%
“…Dieses Ergebnis belegt die eindimensionale Natur der Li + ‐Mobilität in Tavoritstrukturen, wie sie bereits bei den Olivinen beobachtet wurde. Wie bei Olivin‐Materialien blockiert das Vorhandensein von Defekten die 1D‐Kanäle und die Transportgeschwindigkeit wird von der Diffusion des Li + an den Defekten bestimmt . Es wurde gezeigt, dass die Beseitigung von Defekten zu einer signifikanten Verbesserung der elektrochemischen Leistung von LiVPO 4 F führt .…”
Section: Allgemeiner Reaktionsmechanismusunclassified